Application of hold finger therapy in patients with fracture pain: A nursing case study - Kastina, Kastina; Regina, Regina; Apriyadi, Iman (Indonesian Journal of Health Services, 2025)
Background: Fracture-related pain is a common clinical problem experienced by patients following surgical procedures or traumatic injuries, which may hinder recovery and early mobilization. In addition to pharmacological treatment, non-pharmacological interventions are essential as part of holistic nursing care. One relaxation technique that can be implemented by nurses is hold finger therapy, which has the potential to reduce pain perception through relaxation mechanisms and sensory stimulation. Objective: This study aimed to describe the application of hold finger therapy and evaluate its effect on pain intensity in patients with fracture pain using a nursing case study approach. Methods: This study employed a case study design involving two patients with fracture-related conditions, including a post–Open Reduction Internal Fixation (ORIF) malunion of the right humerus and a patient with suspected nasal fracture. Hold finger therapy was administered over three consecutive days with two sessions per day. Pain intensity was measured using the Numeric Rating Scale (NRS) before the intervention and after the final session. Data were analyzed descriptively by comparing pre- and post-intervention pain scores. Results: The findings demonstrated a reduction in pain intensity in both patients following the implementation of hold finger therapy. Pain scores decreased from 7 to 4 in the first patient and from 5 to 2 in the second patient. Patients also reported increased comfort, relaxation, and improved ability to perform gradual mobilization. Conclusion: Hold finger therapy is effective as a non-pharmacological nursing intervention for reducing pain in patients with fracture-related conditions. This technique supports holistic nursing care by enhancing patient comfort and pain control.